Strain wave pathway to semiconductor-to-metal transition revealed by time-resolved X-ray powder diffraction - C. Mariette (Nature Portfolio, 2021)
Ultrafast control of materials draws interest. Here, the authors extend X-ray powder diffraction to the femtosecond timescale to follow the photo-induced semiconductor to metal transition in titanium pentaoxide, observing a phase front that moves at the speed of sound and proposing a little explored mechanism.